Sosialisasi Dan Pendaftaran Nomor Induk Berusaha (NIB) Bagi Masyarakat Dalam Pengembangan Bisnis Di Kelurahan Raja Sebrang - Tika Pranindyastuti (Jurnal Pengabdian Masyarakat Nusantara, 2024)
When the identification was carried out, various problems were found, including poor product development (packaging), labeling that did not meet standards, minimal mastery of digital marketing, financial reports that had not been implemented properly and legalities such as Business Identification Number (NIB) permits that were not yet owned by several actors. MSMEs in Raja Village. Based on this problem, the aim of this activity is the socialization and registration of business identification numbers (NIB) for the community in business development in Raja Seberang Subdistrict. The method used in this activity is the delivery of material and practice in making NIB using OSS. This activity can provide information on the importance of legality such as NIB and other permits so that MSMEs can move up in class and develop following the development of the times and information technology.